A Model‐Based Approach to Design, Organize, and Monitor Dismantling and Decommissioning of Nuclear Facilities. Issue 4 (10th January 2020) - Lafon, Maxence; Chapurlat, Vincent; Milot, Jean‐François; Moitrier, Cyril
ABSTRACT: Dismantling and Decommissioning (D&D) of nuclear facilities involves complex operations, requiring various activities' many stakeholders to collaborate, and must address numerous significant constraints. The CEA (French Alternative Energies and Atomic Energy Commission), is conducting research to better pilot these operations, reduce their costs and timeframes, and improve overall performance. However, many issues remain, leading to studying and implementing, in the form of a method with appropriate tools, systemic principles and complex project and systems engineering. This method first formalizes and specifies the entire requirement set to consider. Second, based on these requirements, the method will enable the project team to structure, check, and demonstrate the project's coherence and feasibility from both the technological and organizational viewpoints. Lastly, the method should permit a constant D&D strategy and product management re‐evaluation, depending on the possible D&D project evolution. Developing demonstration software aims to provide the functionalities requested for the design, and future enterprise software implementation and maintenance, which should provide a complete D&D project Digital Mock‐Up being interoperable and connected to the tools and databases of the stakeholders' information systems.